Capital, Social Reproduction, and the Rise of Inequality. Issue 1 (March 2015) - Spire, Alexis; Gharibian, Arby
Abstract: Thomas Piketty's book has the great merit of implementing a global analysis of inequality that compares countries and periods. However, he adopts a definition of social class that overlooks the importance of cultural capital. Furthermore, the role of social movements is relatively marginalized in his account, which also focuses on fiscal tools to the detriment of other forms of regulation. Nonetheless, this innovative and important book opens up new avenues of research in the field of political sociology.